Juridical Review of The Act of Virtual Money Laundering - Yohanes Fiodas Jaman; Prija Djatmika; Dewi Cahyandari (Yurisdiksi: Jurnal Wacana Hukum dan Sains)
The crime of money laundering as one type of white collar crime has actually been known since 1867. Cyber Money Laundering is money laundering carried out through cyberspace ("mayantara"), so that in addition to committing the crime of money laundering ("money laundering") the perpetrator ("offender") has also committed a crime of mayantara ("cyber crime"), namely committing a crime/crime through a computer system/network. This research method is normative research, normative law research using normative case studies in the form of legal behavior products, for example reviewing the Law. Normatively, cyber money laundering can be caught through Law Number 15 of 2002 concerning the Crime of Money Laundering which was later updated by Law Number 25 of 2003, and last amended by Law Number 8 of 2010 concerning the Prevention and Eradication of the Crime of Money Laundering. Law Number 11 of 2008 concerning Information and Electronic Transactions has not accommodated cyber crime related to economic and financial transactions that are against the law or are not legitimate. In this regard, the readiness of law enforcement officers is very important, both regarding expertise in operating computers, the ins and outs of finance and banking as well as expertise in enforcing cross-territorial laws, which are related to territorial principles with legislative, judicial and executive jurisdictions.